2014
DOI: 10.1097/ppo.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

Current and Proposed Molecular Diagnostics in a Genitourinary Service Line Laboratory at a Tertiary Clinical Institution

Abstract: The idea that detailed knowledge of molecular oncogenesis will drive diagnostic, prognostic, and therapeutic clinical decision making in an increasingly multidisciplinary practice of oncologic care has been anticipated for many years. With the recent rapid advancement in our understanding of the molecular underpinnings of genitourinary malignancies, this concept is now starting to take shape in the fields of prostate, kidney, bladder, testicular, and penile cancer. Such breakthroughs necessitate the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 84 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…The recurrent chromosomal loss we observed by exome sequencing supports a recent study by Peckova et al (16) that reported similar recurrent chromosomal losses using array CGH and FISH strategies. Importantly none of the samples in this cohort with pure MTSCC histology displayed chromosomes 7 and 17 gains, commonly noted as gains in type I papillary RCC(17). The recent TCGA papillary RCC (KIRP) study reported Hippo pathway mutations ( NF2 and SAV1 ) in 4% of the samples and used CNV to classify tumors into 3 groups such as genome stable, unstable and chromosome 7/17 gains(2).…”
Section: Resultsmentioning
confidence: 87%
“…The recurrent chromosomal loss we observed by exome sequencing supports a recent study by Peckova et al (16) that reported similar recurrent chromosomal losses using array CGH and FISH strategies. Importantly none of the samples in this cohort with pure MTSCC histology displayed chromosomes 7 and 17 gains, commonly noted as gains in type I papillary RCC(17). The recent TCGA papillary RCC (KIRP) study reported Hippo pathway mutations ( NF2 and SAV1 ) in 4% of the samples and used CNV to classify tumors into 3 groups such as genome stable, unstable and chromosome 7/17 gains(2).…”
Section: Resultsmentioning
confidence: 87%
“…HER2 expression can be determined using different methods, such as IHC, enzyme-linked immunosorbent assay, fluorescent (FISH), and PCR [40]; both IHC and ISH are considered among current molecular diagnostics tools in a Genitourinary Service Line Laboratory at a Tertiary Clinical Institution [41].…”
Section: Issues In Her2 Assessment Methodsmentioning
confidence: 99%
“…Numerous long noncoding RNAs (lncRNAs) have recently emerged as targets for clinical translation [1,2]. We previously identified 121 novel, differentially expressed prostate cancer (PCa) lncRNAs, including SChLAP1, which is overexpressed in a subset of tumors and associated with more aggressive disease [35].…”
mentioning
confidence: 99%